Low rates of radiographic progression of structural joint damage over 2 years of baricitinib treatment in patients with rheumatoid arthritis - Désirée van der Heijde; Yoshiya Tanaka; Paul Emery; Li Xie; Michael Schiff; Gabriella Meszaros; Taeko Ishii; Marta Casillas; Robert A Ortmann (RMD Open, 2019)
Objectives To evaluate radiographic progression of structural joint damage over 2 years in patients with rheumatoid arthritis from baricitinib clinical trials who were disease-modifying antirheumatic drug (DMARD)–naïve or had an inadequate response to conventional synthetic DMARDs (csDMARD-IR).Methods Patients had completed one of three phase III studies and entered a long-term extension (LTE) study, continuing on the same baricitinib dose as at originating study completion. At 52 weeks, DMARD-naïve patients receiving methotrexate (MTX) or combination therapy (baricitinib 4 mg+MTX) were switched to baricitinib 4 mg monotherapy (±MTX per investigator opinion); MTX-IR patients receiving adalimumab were switched to baricitinib 4 mg on background MTX. At 24 weeks, csDMARD-IR patients receiving placebo were switched to baricitinib 4 mg on background csDMARD. Radiographs at baseline, year 1 and year 2 were scored using the van der Heijde modified Total Sharp Score. Linear extrapolation was used for missing data.Results Of 2573 randomised patients, 2125 (82.6%) entered the LTE, of whom 1893 (89.1%) entered this analysis. At year 2, progression was significantly lower with initial baricitinib (monotherapy or combination therapy) versus initial MTX in DMARD-naïve patients (proportion with non-progression defined by ≤smallest detectable change (SDC): 87.3% baricitinib 4 mg+MTX; 70.6% MTX; p≤ 0.001). In MTX-IR patients, progression with initial baricitinib was significantly lower than with initial placebo and similar to initial adalimumab (≤SDC: 82.7% baricitinib 4 mg; 83.5% adalimumab; 70.6% placebo; p≤0.001). In csDMARD-IR patients, significant benefit was seen with baricitinib 4 mg (≤SDC: 87.2% vs 73.2% placebo; p≤0.01).Conclusions Treatment with once-daily baricitinib resulted in low rates of radiographic progression for up to 2 years.